The Impact of Organizational Behavior on Member Performance in the Sociology Education Student Association at Makassar State University - Dipoatmodjo, Tenri Sayu Puspitaningsih (PT Maju Malaqbi Makkarana, 2024)
This study aims to determine whether organizational behavior will affect organizational performance and whether there is no influence of organizational behavior on organizational performance. This research uses descriptive qualitative method. By conducting interviews with two members of the association who have different positions, namely the treasurer and staff of the organization's association. Based on the results of the interviews that have been conducted, it shows that within the Sociology Education Student Association organization, Makassar State University, there is an influence of organizational behavior that has had an impact on organizational performance. . This impact depends on individual behavior in the organization because it is the individual who will run the organization to achieve the desired goals. Therefore in the organization must have positive individual behavior in carrying out organizational goals. it can be concluded based on the conclusions above according to the interviews of the two members, namely organizational behavior is important for every organization to encourage positive behavior and build a work climate that supports achieving long-term success.